Touching Technology-Parents' Experiences of Remote Consultations for Children With Severe Congenital Cardiac Conditions: Quasi-Experimental Cohort Study - Julie Elizabeth May McCullough; Marlene Sinclair; Jonathan Gillender; Brian McCrossan; Paul F Slater; Rosie Browne; Frank Casey (JMIR Publications, 2024)
Abstract BackgroundRemote consultations (RCs) using videoconferencing was recommended by the General Medical Council as the method for clinicians to provide patient consultations during the COVID-19 pandemic. Facilitating this while providing high-quality care depends on the usability and acceptability of the technology. ObjectiveThis project aimed to investigate parents' experiences of using videoconferencing technology for real-time RCs with children who had congenital heart defects during the COVID-19 pandemic lockdown. MethodsThis study's design was quasi-experimental and was underpinned by the Unified Theory of Acceptance and Use of Technology model that seeks to explain and predict an individual's intention to use a technology. Parents were informed of this study by the medical team, posters were made available in the wards and clinics, and leaflets were left for browsing. Clinician screening of potential participants led to the identification of 33 children and parents who were enrolled on this study. The intervention was a web-based RC by medical staff using a secure, interactive videoconferencing platform (Pexip). Each child and their mother or father received 8 RCs with the same specialist doctor or nurse. Measurements were taken using web-based questionnaires pre and post consultation at the first, middle, and last events; questions were focused on the acceptability, usability, and clinical applicability of RCs. Parents' experiences were explored using recorded interviews and analyzed thematically. ResultsIn total, 29 children aged 4‐1052 (mean 95, SD 191.14) days completed the project, receiving a total of 189 RCs as part of their routine care. Parents' prior experience of consultation via videoconference was low; however, as time progressed, their use and acceptance of the technology increased. The intervention was warmly received by all parents who found the face-to-face component particularly useful for discussion with their child's medical team. Furthermore, parents noted the savings on time, money, and childcare. ConclusionsWhile in-person consultations are considered the gold standard of patient care, increasing pressures on health services and staff reduce availability. Given the ease of access and additional benefits experienced by parents and their children, it is proposed that hybrid models of consultation and care provision are equal, if not superior, to in-person consultations in the management of children with severe congenital heart defects while reducing costs and pressure on the health service and parents.